Chronic Obstructive Pulmonary Disease Patients Have Increased Levels of Plasma Inflammatory Mediators Reported Upregulated in Severe COVID-19 - Acevedo, Nathalie; Escamilla-Gil, Jose Miguel; Espinoza, Héctor; Regino, Ronald; Ramírez, Jonathan; Florez de Arco, Lucila; Dennis, Rodolfo; Torres-Duque, Carlos A.; Caraballo, Luis (Frontiers in Immunology, 2021)
Background Chronic obstructive pulmonary disease (COPD) is associated with increased risk of severe COVID-19, but the mechanisms are unclear. Besides, patients with severe COVID-19 have been reported to have increased levels of several immune mediators. Methods Ninety-two proteins were quantified in 315 plasma samples from 118 asthmatics, 99 COPD patients and 98 healthy controls (age 40-90 years), who were recruited in Colombia before the COVID-19 pandemic. Protein levels were compared between each disease group and healthy controls. Significant proteins were compared to the gene signatures of SARS-CoV-2 infection reported in the “COVID-19 Drug and Gene Set Library” and with experimentally tested protein biomarkers of severe COVID-19. Results Forty-one plasma proteins showed differences between patients and controls. Asthmatic patients have increased levels in IL-6 while COPD patients have a broader systemic inflammatory dysregulation driven by HGF, OPG, and several chemokines (CXCL9, CXCL10, CXCL11, CX3CL1, CXCL1, MCP-3, MCP-4, CCL3, CCL4 and CCL11). These proteins are involved in chemokine signaling pathways related with response to viral infections and some, were found up-regulated upon SARS-CoV-2 experimental infection of Calu-3 cells as reported in the COVID-19 Related Gene Sets database. An increase of HPG, CXCL9, CXCL10, IL-6, MCP-3, TNF and EN-RAGE has also been experimentally detected in patients with severe COVID-19. Conclusions COPD patients have altered levels of plasma proteins that have been reported increased in patients with severe COVID-19. Our study suggests that COPD patients have a systemic dysregulation in chemokine networks (including HGF and CXCL9) that could make them more susceptible to severe COVID-19. Also, that IL-6 levels are increased in some asthmatic patients (especially in females) and this may influence their response to COVID-19. The findings in this study depict a novel panel of inflammatory plasma proteins in COPD patients that may potentially associate with increased susceptibility to severe COVID-19 and might be useful as a biomarker signature after future experimental validation.